Coordination of the Uptake and Metabolism of Amino Acids in Mycobacterium tuberculosis-Infected Macrophages - Jiang, Qingkui; Shi, Lanbo (Frontiers in Immunology, 2021)
Abstract Macrophage polarization to the M1-like phenotype, which is critical for the pro-inflammatory and antimicrobial responses of macrophages against intracellular pathogens, is associated with metabolic reprogramming to the Warburg effect and a high output of NO from increased expression of NOS2. However, there is limited understanding about the uptake and metabolism of other amino acids during M1 polarization. Based on functional analysis of a group of upregulated transporters and enzymes involved in the uptake and/or metabolism of amino acids in Mycobacterium tuberculosis-infected macrophages, plus studies of immune cell activation, we postulate a coherent scheme for amino acid uptake and metabolism during macrophage polarization to the M1-like phenotype. We describe potential mechanisms that the increased arginine metabolism by NOS2 is metabolically coupled with system L transporters LAT1 and LAT2 for the uptake of neutral amino acids, including those that drive mTORC1 signaling toward the M1-like phenotype. We also discuss the underappreciated pleiotropic roles of glutamine metabolism in the metabolic reprogramming of M1-like macrophages. Collectively, our analyses argue that a coordinated amino acid uptake and metabolism constitutes an integral component of the broad metabolic scheme required for macrophage polarization to M1-like phenotype against M. tuberculosis infection. This idea could stimulate future experimental efforts to elucidate the metabolic map of macrophage activation for the development of anti-tuberculosis therapies.